(3eYGjjQ GdJbGQjQ GdeGdjI GdOhdjI (B2007s - (3NGdO LeGd(B, (3GdLYGQGJs ((3YeGf(B:s (3GKQGA ddfTQ h GdJhRjY(B,s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3NdajI YGeI Yf eYGjjQ GdJbGQjQ GdeGdjI GdOhdjI,GdbhGFe GdeGdjI,GdbhGFe GdeGdjI GdehMOI, GdCOhGJ GdeGdjI, GdYedjGJ GdQCSeGdjI h GdJehjdjI,GdYedjGJ GdEjQGOjI,GdedMbGJ(B. s
(3HjHdjhZQGajG U(B.549 (3edGMb U(B.537s
Keywords: (3JbGQjQ eGdjIs; (3eGdjI YGeIs; (3eYGjjQ GdeMGSHI GdOhdjIs